Law enforcers recognition level emerging threats based on physical appearance and behavior signs the enemy - R.M. Radzievskiy; V.I. Plisko (Physical Education of Students, 2015)
Purpose: examine the effectiveness of the training method of differential approach to the choice of means of influence on the action of law enforcers opponent with different levels of aggressiveness. Material : the experiment involved 15 students of the Kyiv National Academy of Internal Affairs and the 15 employees of the State Guard of Ukraine. Results : presented curriculum for special physical and tactical training. The program details the conceptual apparatus of THREATS and DANGERS manifestations of different levels of aggressiveness opponent (case analysis of its motor behavior). The study participants underwent 7 day course focused training. The basis of the course is an advanced theoretical base. The base is aimed at developing knowledge and skills of employees in determining the level of danger. Including threats from testing and modeling episodes of extreme situations the options cadets. Conclusions : In the simulated collision situations with aggressive opponent to the students significantly improved the adequacy of the response to the threat of execution time and within the legal grounds. Recognition was determined by the level of aggressiveness manifest manners enemy, his emotions, motivation, motor behavior, positional arrangement for 2 - 3 seconds. The program contributed to the development of qualities: attention, orientation, perception, motor lead.